Analisis Kompetensi Pedagogik Guru Terhadap Motivasi Belajar Siswa Di Kelas VII MTs Muhammadiyah Al Fatah Nangahale - Dahlia, Dahlia; Mohammad Fitri; Muhammad Syahrun (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the pedagogical competence of teachers in class VII MTs Muhammadiyah Al Fatah Nangahale and to determine student learning motivation in class VII MTs Muhammadiyah Al Fatah Nangahale. By using descriptive qualitative. Primary data from this study came from subject teachers, head of Madrasah, students. Meanwhile, secondary data using supporting documents of this research are learning tools, profiles, vision and mission. The data collection techniques used are interviews, observation and documentation. To analyse the data, researchers carried out activities in data analysis, namely data reduction, data presentation, and conclusion drawing.The results of this study indicate that pedagogic competence in the category is quite good, namely the competence of mastering the characteristics of students and curriculum development competencies, communication competencies with students while pedagogic competence in the category is lacking, namely the competence of mastering learning theory and the principles of educational learning, the competence of educational learning activities, the competence of developing the potential of students, as well as the competence of assessment and evaluation and student learning motivation at MTs Muhammadiyah Al Fatah Nnagahale can be said to be still low.